Numerical framework for multi-pass SMAW pre-WPS development on SA-36 low carbon steel - Regan Rahadian Pambudi; Ayende Ayende (Politeknik Negeri Lhokseumawe, 2026)
Multi-pass SMAW on low carbon steel demands precise parameter control to ensure joint integrity and qualification compliance. Trial-and-error WPS development is material-intensive and time-consuming, particularly where heat input management across passes is critical. This study proposes a numerical framework combining Carbon Equivalent (CET) analysis, Rosenthal 2D thermal modeling via MATLAB with SmartWeld suite, and thermo-mechanical FEA to determine preliminary welding parameters prior to experimental qualification. Parameters are validated on SA-36 plate using a 4-pass SMAW procedure qualified under ASME BPVC Section IX, with NDT per ASME BPVC Section V. Tensile strengths of 530.90 MPa and 503.99 MPa exceed the 400 MPa minimum, all bend specimens pass without rejectable discontinuities, and FEA deformation prediction of 1.59 mm against a measured 2.01 mm demonstrates conservative predictive capability suitable for preliminary parameter screening. Unlike conventional trial-and-error qualification, this framework integrates three analytical methods into a structured pre-screening workflow, reducing material consumption and qualification iterations prior to experimental testing.